O uso variável das construções condicionais em contextos de aquisição de tradições discursivas da escrita - Ferro, Fernanda Meneghetti [UNESP] (2015)
The aim of this research, by focusing on the conditional conjunction as a study object, is to investigate the process of introducing young writers attending junior high school at a public school in São José do Rio Preto (SP), Brazil, to the idiomatic techniques and discursive techniques of language, in terms of Koch (1997) and Öesterreicher (1997), throughout the learning and development process of writing. On the axis of idiomatic techniques, we study the different ways processes of conditional conjunction occur, according to the syntactic, semantic and pragmatic domains (HALLIDAY, 1985; KORTMANN, 1997; SWEETSER, 1990), and on the axis of discursive techniques, we study possible correlations between discursive traditions of writing and variable conditional conjunction frameworks (KABATEK, 2005; LONGHIN-THOMAZI, 2011). Based on the systemic-functional conjunction model proposed by Halliday (1985), in addition to studies by Kortmann (1997) and Sweetser (1990), we conceive that conditional constructions are realized through different syntactic arrangements and include semantic and pragmatic polysemy on the axis of meaning. Additionally, we consider the conditional conjunction frameworks to surpass the logical domain, given that they function as discursive persuasion resources, involving the intentions of the discourse participants (FILLENBAUM, 1986; HIRATA-VALE & OLIVEIRA, 2003; PAIVA & BRAGA, 2010). From this perspective, we analyze the conditional conjunction processes by intersecting the options on the tactical axis, in which we recognize paratactic and hypotactic conjunction mechanisms, and by investigating the axis of meaning relations, in which we discuss the fluid boundaries between the conditional relation and the sense of time/mode/alternation. Additionally, we study the conditionals according to the domains of content, epistemics and acts of speech (SWEETSER, 1990), highlighting the discursive and pragmatic functions which ...